Variability of the synoptophore for measuring fusional vergence in intermittent exotropia - Kumar, Rajesh; Vyas, Malhar; Passi, Neebha (Journal of Neonatal Surgery, 2025)
Background: To determine the variability of the synoptophore in children with IXT. The study demonstrates that the synoptophore effectively measures the near-positive fusional vergence (PFV) breakpoint, although variability exists in distance PFV breakpoint measurements. Aim: The study aims to evaluate the repeatability of synoptophore measurements, focusing on blur, break, and recovery points of positive and negative fusional vergence (PFV and NFV) at near and distance fixation in children diagnosed with intermittent exotropia (IXT). Material and Methods: Ninety-eight IXT subjects, aged 6 to 16, were examined. Measurements of near and distance PFV and NFV blur, break, and recovery points were conducted with a synoptophore across two visits, spaced 24 hours apart, involving the same examiner, environment, and testing conditions. The intra-class correlation coefficient (ICC), smallest detectable change (SDC), and coefficient of repeatability (CR) were calculated for these measures. Result: The PFV break point ICC has excellent near reliability (0.90) and moderate distant reliability (0.67). SDC (14.1), CR (19), and ICC (0.90) demonstrated a consistent synoptophore near PFV breakpoint. The ICC PFV recovery points demonstrated reliable performance at both distances, with moderate reliability (0.69) at near distances and good reliability (0.80) at distance for NFV breakpoints. Between visits, the near NFV recovery point was consistent with ICC (0.83), SDC (13.8), and CR (±16), showing good reliability. Conclusion: The study found that the synoptophore provides consistent and reliable assessments of the near PFV breakpoint; however, other near and distant FV parameter measurements show low repeatability.